Efeito da bradicinina na reatividade vascular sob influência do fenótipo da enzima conversora de angiotensina I (ECA - E.C. 3.4.15.1) - Guimarães, Thales Henrique Santos [UNIFESP] (2017)
In previous studies of the group, it was found that female rats from 2-BAW colony features the plasma angiotensin-converting enzyme (ACE) activity with very outliers, but constant for each animal. This fact made it possible to divide these animals into three groups according to the levels of this enzyme: animals with high ACE activity (ECAa), with intermediate ACE activity (ECAi) and low ACE activity (ECAb). Heredity phenotypes were proven, which led to the establishment of a new strain of animals: Wistar/INFAR/ECAa and Wistar/INFAR/ECAb. However, The blood pressure of the animals, were not different between the phenotypes, a puzzling fact taking into account the participation of the renin-angiotensin-aldosterone system (RAAS) and the kallikrein-kinin system (KKS) in maintaining blood pressure. From these data, this study aims to analyze the effect of bradykinin and other kinins in the vascular reactivity of these rats with different phenotypes of ACE using agonists and antagonists of the parasympathetic nervous system (SNP), RAAS and KKS. Therefore, we evaluated the participation of these systems in vitro in thoracic aorta of male rats ECAa and ECAb. In the study of acetylcholine in the presence and absence of atropine it was not possible to detect significant differences between phenotypes and in the presence of atropine, showed a vasodilator concentration-dependent blocked response. In the analysis of the KKS using bradykinin (BK), we observed a similar hypotensive effect between phenotypes and when preincubated the B2 receptor antagonist of bradykinin (HOE-140), we observed a significant reduction of the vasodilatory effect (Emax) concentration-dependent, indicating thus the response of bradykinin might be mediated mainly via the B2 receptor. Also about bradykinin, we found that its action takes place predominantly via nitric oxide (NO) because when pre-incubated the NOS inhibitor (L-NAME), a significant reduction of vasorelaxant response was observed, but again, with no significant differences between phenotypes. It was also studied the action of des-Arg9-BK, an active BK-metabolite, which was possible to observe a response very similar to BK, although with a lower Emax, thus suggesting a lower affinity and activation of the B2 receptor, which is expressed constitutively. In the study of phosphorylated kinin we observed a decreased response of the phophorylated bradykinin compared to non-phosphorylated form, indicating a direct effect of the phosphate group (-PO3H2) in the interaction and activation of kinin receptors. Finally, we determined the vasodilator response of Ang (1-7), as well as its influence on bradykinin, which potentiated the vasodilatory action of BK, but with no differences between the phenotypes. In conclusion, the findings of this study serve to highlight that although these animals have different phenotypes (ECAa, ECAb), they do not have distinct responses to these vasodilators, ie the enzymatic phenotypes of ACE does not seem to influence the final responses of the vasoactive substances studied, due possibly exist compensatory mechanisms by alternative pathways different of the RAAS and KKS.